The Influence of Social Environment, Locus of Control, Love of Money, Parental Income on the Financial Behavior of Economics and Business Faculty Students in Pontianak City - Syakira, Vinanty Tri; Suryadi, Edy (International Journal of Science and Society, 2024)
Financial behavior is an important issue, especially with consumptive behavior that tends to lead to financial irresponsibility. Pontianak City's faculty of economics and business students should be able to solve financial problems. The university environment should provide financial understanding, especially for students of the Staff of Monetary viewpoints and Business. The model in this study relied upon the going with guidelines: (1) students of a staff of economy and business semester 4 to 8 who are dynamic close by in Pontianak. The looking at strategy for this study is purposive investigating. The study was conducted using a standardized sample size of 15,138 students. As indicated by the information investigation and conversation, monetary way of behaving is decidedly affected by friendly climate and locus of control. Locus of control, love of money, and parental income also play a role in shaping students' financial behaviors.